'Words for music perhaps': W.B. Yeats and musical sense - Paterson, A (2007)
‘Poetry’ insisted Ezra Pound, ‘is a composition of words set to music’: his Cantos remembered ‘Uncle Willie’ downstairs composing, singing poetry to himself. This study examines the nature and effects of W.B.Yeats’s idiosyncratic but profound sense of music. For his poems were compositions set to music. They were saturated with musical themes; syntactically he professed to write for the ear rather than the eye; and he flung himself repeatedly into the breach between music and words, composing ballads, songs, and plays with music, and performing poetry with musical instruments. My thesis is that nature of poetry, spoken, read or sung, obsessed Yeats, and I hold it self evident that such an acutely self-conscious poetry will articulate this obsession: to use his own imagery, will bear the scars of its own birth. What follows is a study of meaning, obsession, and influence, beginning with what Yeats knew and how he came to poetry: his father’s and his own vocalizations of the musical preoccupations of Scott and Shelley, viewed through the annotations of ‘the first book [he] knew Shelley in’ and the solipsistic singers and instrumentalists of his early verse. The theme of chapter two is Ireland: the musical resonances of Anglo Irish ballads and Irish verse are viewed through Yeats’s aurally-oriented canon-formation, as we examine his instinctual recitations and deliberate approach to Irish folksong through the mediation of Douglas Hyde. The aesthetics of Wagner, Pater, and the French symbolistes frame the third chapter, which describes how poetry might approach the condition of music in the motivic organization of The Wind Among the Reeds. In chapter four the impact of Nietzsche’s profoundly musical philosophy is correlated for the first time with the exact moments of Yeats’s discovery of his texts, as Yeats’s plays and poetry move from ‘Apollonian’ languor to ‘Dionysian’ energy, from dream to song and dance. My final chapter uncovers the long history of the practical experiments Yeats made to perform poetry with a ‘psaltery’, and their resonating afterlife in subsequent poetry and poets. No musician himself, Yeats’s musical sense has until now been entirely dismissed: this study shows how central it is to his art and to an understanding of the dominant aesthetic of the age.